Penerapan Layanan Informasi Menggunakan Media Audio Visual untuk Meningkatkan Minat Belajar Siswa - Annisa Walindarahma, Sri; Rozzaqyah, Fadhlina; Qonita, Fatiah (Universitas PGRI Palembang, 2025)
This study aims to increase students' learning interest through the implementation of information services using audio-visual media in class VIII.3 of SMP Negeri 57 Palembang for the 2024/2025 academic year. This research is a Guidance Service Action Research (Penelitian Tindakan Layanan/PTL) conducted in two cycles, involving 30 students as the subjects. Data analysis techniques used include percentage calculations and paired T-Test analysis. The results showed a significant increase in students' learning interest in each cycle. In the pre-test stage, the average score was 90.6 with a percentage of 57% (moderate category). After the intervention in the first cycle, the average increased to 109.4 (68%, high category), and in the second cycle, it further increased to 130.4 (82%, high category). This improvement indicates that information services delivered through audio-visual media have a positive impact on enhancing students' learning interest. Therefore, guidance and counseling services, particularly information services using audio-visual media, can be an effective strategy to foster student interest and active engagement in the learning process.